Investor Behavior 2014
DOI: 10.1002/9781118813454.ch1
|View full text |Cite
|
Sign up to set email alerts
|

Investor Behavior: An Overview

Abstract: Crowd psychology, panics, and financial schemes Historical financial crisesNote: This exhibit provides a chronological timeline of a sample of relevant books in financial history and investment theory from 1841 to 1978. These books cover a wide range of subject matter including: crowd psychology, group behavior, individual behavior panics, bubbles, crashes, speculative behavior, investor psychology, trader psychology, investment strategies and theories, financial mistrust, and investor personality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 25 publications
1
31
0
5
Order By: Relevance
“…In recent years, the rational actor model has been called into question by research in the nonbusiness fields of behavioral psychology, cognitive science, experimental philosophy, and others that demonstrate that human decision making is often far from rational (Gilovich, Griffin, & Kahneman, ; Kahneman, ). Even in business schools, the limitations of the rational actor model have been acknowledged by the rise of the new fields of behavioral finance (Baker & Ricciardi, ) and behavioral economics (Camerer, Loewenstein, & Rabin, ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the rational actor model has been called into question by research in the nonbusiness fields of behavioral psychology, cognitive science, experimental philosophy, and others that demonstrate that human decision making is often far from rational (Gilovich, Griffin, & Kahneman, ; Kahneman, ). Even in business schools, the limitations of the rational actor model have been acknowledged by the rise of the new fields of behavioral finance (Baker & Ricciardi, ) and behavioral economics (Camerer, Loewenstein, & Rabin, ).…”
Section: Introductionmentioning
confidence: 99%
“…In truth, the fi rst type of agents are more inclined to accompany impressions of self-management and cognitive change and can also be capable of dealing with negative feelings in a way that allows them to maintain objectivity and pursue long-term objectives. Baker and Ricciardi (2014) confi rm these fi ndings, stating that experienced and mature investors know that success depends on controlling emotions and overcoming preconceptions. Th is helps them to avoid the typical errors of new investors related to excessive confi dence.…”
Section: Theoretical Frameworkmentioning
confidence: 88%
“…Th e studies from Baker and Ricciardi (2014) and Fenton-O'Creavy, Soane, Nicholson, and Willman (2011) present results that indicate that investor emotion is a critical factor in investment decision-making. Fenton-O'Creavy et al (2011) carried out a study with a sample of London investors in investment banks and observed that eff ectively regulating emotions appears to be a critical factor in successful investment and trading decisions.…”
Section: Theoretical Frameworkmentioning
confidence: 92%
See 2 more Smart Citations